Software frameworks in biomedical informatics: A systematic review and research agenda - Al-Bashayreh, Mahmood Ghaleb; Hashim, Nor Laily; Khorma, Ola Taiseer (2013)
Design of Mobile Patient Monitoring Frameworks (MPMF) is an emerging study in the biomedical informatics domain.However, literature about this topic remains fragmented: first, there are no categories in the literature to characterize these MPMF; second, there are no success factors that must be satisfied to enhance the design of these MPMF; third, there is a need for a research agenda that provides a foundation for further research and development to enhance the design of these MPMF.To address this gap, this paper reviews software frameworks in general and conducts a systematic review of 20 designed frameworks in the biomedical informatics domain.Consequently, this paper provides three results.First, it identifies a number of categories to be used to gain an intensive and extensive understanding of the designed MPMF.Second, it identifies a set of success factors, called Factors of Successful Application Frameworks (FSAF), to be used to enhance the design of MPMF.Third, it presents a research agenda that shows lacks and gaps in the designed MPMF and provides a foundation to help researchers design enhanced MPMF.The results show that, as of yet, there is no study integrating all the FSAF to enhance the design of MPMF.Therefore, there is a need for further research to enhance the existing MPMF design.